The Globalization of Science: The Place of Agricultural Research - Bonte-Friedheim, Christian H.; Sheridan, Kathleen (International Service for National Agricultural Research, 1997)
This book presents 25 thought-provoking papers contributed by leaders of the CGIAR on their vision of global agricultural research and some of the major issues, priorities, and structures required for the future. The authors have dealt with some very important aspects of the globalization of agricultural research, especially regarding the past and future role of the CGIAR.The rather uniform central message that runs throughout cannot be ignored: without more and more effective and efficient agricultural research at all levels, and without global partnerships, we will never meet the challenges of feeding the hungry, providing a living for the poor, sustaining and protecting our natural heritage, and providing the basis for all of us to live in comfort and security. The action to meet these challenges must start now.